Positifikasi Hukum Islam di Indonesia: Prospek dan Problematikanya - Sodiqin, Ali (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2012)
Implementation of Islamic law in Indonesia has any problems, internal aspectand external one. In reality, the relationship between Islam and the state have caused afriction of interests between of moslem in one side and the state in another. As areligion, Islam put all its norms into effect for its adherents,meanwhile the state isimpossible to conduct rule of law from one religion. In other hand, institutionalizationof Islamic law faced two problems, firstly,related to the position of Islamic law in thenational law, and secondly, related to internal aspect of Islamic law. These problems areimplicate to the developmental prospect of Islamic law in Indonesia. The suggestedfactors of Islamic law are majority in adherents, widely the object,and supporting ofIslamic organizations. The handicaps of implementing of Islamic law are uncompletelyin its institutionalization, and dichotomy of Islamic thought, and influence ofunstability political law in Indonesia.